Discovery of novel pyrazole-containing benzamides as potent RORγ inverse agonists. Issue 15 (1st August 2015) - Wang, Tao; Banerjee, Daliya; Bohnert, Tonika; Chao, Jianhua; Enyedy, Istvan; Fontenot, Jason; Guertin, Kevin; Jones, Howard; Lin, Edward Y.; Marcotte, Douglas; Talreja, Tina; Van Vloten, Kurt
Graphical abstract: Abstract: The nuclear receptor RORγ plays a central role in controlling a pro-inflammatory gene expression program in several lymphocyte lineages including TH17 cells. RORγ-dependent inflammation has been implicated in the pathogenesis of several major autoimmune diseases and thus RORγ is an attractive target for therapeutic intervention in these diseases. Starting from a lead biaryl compound4a, replacement of the head phenyl moiety with a substituted aminopyrazole group resulted in a series with improved physical properties. Further SAR exploration led to analogues (e.g., 4j and5m ) as potent RORγ inverse agonists.